Perilaku Konsumtif Gen Z dan Kesadaran Keamanan Digital dalam Ekonomi Digital Indonesia - Diky Budiman; Yudi Sutrasna; Sakum, Sakum (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
This study aims to examine the consumptive behavior of Generation Z within the context of digital security awareness and its implications for the digital economy in Indonesia. Using a literature review methodology, this research collects and analyzes theories from various supporting academic articles. The findings indicate that digital security awareness plays a crucial role in shaping more responsible and sustainable consumption behaviors in digital spaces. Additionally, the convenience offered by digital transactions must be accompanied by improved digital literacy and a stronger understanding of data privacy. These factors are essential in strengthening trust and ensuring the sustainability of the digital economy ecosystem among Generation Z. This study contributes a new perspective by integrating the dimensions of consumptive behavior and digital security into the analysis of young people's economic behavior in the era of digital transformation. It is the first study to simultaneously integrate three dimensions consumptive behavior, cybersecurity awareness, and the digital economy within the Indonesian Gen Z context. In Indonesia, the rapid rise of digital transactions has not been fully matched by improvements in digital security literacy. This gap creates a paradox in which fast digital economic growth coexists with increasing potential security vulnerabilities.